ANALISIS RISIKO PROFIL DAN PENGARUHNYA TERHADAP PROFITABILITAS PADA BANK BUMN - Ambardi, Ambardi; Alim, Mulia; Aminah, Aam; Helmi, Helmi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study is to analyze the risk profile and its impact on profitability at state-owned banks. The sampling technique used in this study is Nonprobability Sampling, namely Purposive Sampling. The population and samples used in this study are state-owned banks, namely Bank BNI, Bank Mandiri, Bank BRI, and Bank BTN by taking data from annual financial reports published from 2017 to 2022. The data analysis technique used is descriptive statistical analysis and statistical analysis. statistics. Descriptive statistical analysis was used to describe the variables in this study, namely Non Performing Loans (NPL), Loan to Deposit Ratio (LDR) and Return on Assets (ROA). The statistical analysis used was multiple linear regression panel data tests which were first tested for model selection, then added the classic assumption test as a condition for using regression analysis. Furthermore, F statistical tests and t statistical tests (hypothesis testing) were carried out, the coefficient of determination. The results of this study are that NPL or non-performing loans have no significant negative effect on ROA at state-owned banks. From the NPL value, it can also be concluded that 3 state-owned banks, namely BNI, Mandiri and BRI, have relatively good NPL levels, meaning that the risk of bad credit is low, except for BTN banks. As for the LDR or Loan to Deposit Ratio, there is no significant effect on ROA at government banks.